Putative neuroprotective pharmacotherapies to target the staged progression of mental illness. Issue 5 (28th January 2019) - Robertson, Oliver D.; Coronado, Nieves G.; Sethi, Rickinder; Berk, Michael; Dodd, Seetal
Abstract : Aim: Neuropsychiatric disorders including depression, bipolar and schizophrenia frequently exhibit a neuroprogressive course from prodrome to chronicity. There are a range of agents exhibiting capacity to attenuate biological mechanisms associated with neuroprogression. This review will update the evidence for putative neuroprotective agents including clinical efficacy, mechanisms of action and limitations in current assessment tools, and identify novel agents with neuroprotective potential. Method: Data for this review were sourced from online databases PUBMED, Embase and Web of Science. Only data published since 2012 were included in this review, no data were excluded based on language or publication origin. Results: Each of the agents reviewed inhibit one or multiple pathways of neuroprogression including: inflammatory gene expression and cytokine release, oxidative and nitrosative stress, mitochondrial dysfunction, neurotrophin dysregulation and apoptotic signalling. Some demonstrate clinical efficacy in preventing neural damage or loss, relapse or cognitive/functional decline. Agents include: the psychotropic medications lithium, second generation antipsychotics and antidepressants; other pharmacological agents such as minocycline, aspirin, cyclooxygenase‐2 inhibitors, statins, ketamine and alpha‐2‐delta ligands; and others such as erythropoietin, oestrogen, leptin, N‐acetylcysteine, curcumin, melatonin and ebselen. Conclusions: Signals of evidence of clinical neuroprotection are evident for a number of candidate agents. Adjunctive use of multiple agents may present a viable avenue to clinical realization of neuroprotection. Definitive prospective studies of neuroprotection with multimodal assessment tools are required.